High-grade endometrial stromal sarcoma after treatment with tamoxifen in a patient treated for breast cancer. Issue 5 (1st August 2003) - Saga, Y.; Ohwada, M.; Kohno, T.; Takayashiki, N.; Suzuki, M.
Abstract : Tamoxifen has been widely used in breast cancer treatment. In recent years, the occurrence of uterine malignancies in patients receiving long-term tamoxifen therapy has attracted attention. Most of these malignancies are endometrial adenocarcinomas, but low-grade endometrial stromal sarcomas have occasionally been reported. Here we report a woman who developed a high-grade endometrial stromal sarcoma after receiving postmastectomy tamoxifen therapy. The patient underwent a left mastectomy at age 45 and subsequently received oral tamoxifen for 3 years. At age 51, she was diagnosed with endometrial stromal sarcoma, for which a radical hysterectomy was performed. High-grade endometrial stromal sarcoma was diagnosed by postoperative histologic examination. Immunostaining for the estrogen receptor was negative in sarcoma cells, but positive in the residual endometrial epithelium and the nucleus of adjacent stromal cells within the tumor. The patient has now survived disease-free for 37 months after surgery.